Considered in context: EFL teachers' views on the classroom as a bilingual space and codeswitching in shared-L1 and in multilingual contexts. (July 2020) - Gallagher, Fiona
Abstract: This paper describes a qualitative research study which explores the views and practices of EFL teachers in relation to codeswitching and the use of the L1 in the classroom and the extent to which their particular teaching context plays a role in this. Interviews took place with twenty-four teachers who teach or have taught English in both (1) multilingual contexts in which the learners typically do not share a common L1 and (2) contexts in which the learners typically share an L1 other than English. Themes relating to the nature of the teaching and learning space in each context, the extent to which the teachers view the teaching environment as a bi/multilingual setting, and the role of the particular context in their overall approach and practices are examined. Findings point to the largely flexible, fluid and mixed views of EFL teachers in relation to the use of the L1 in the classroom and to the need for a more explicit focus on this area in teacher development and training. It is suggested that taking a bilingual stance may offer potential as a means for teachers to reflect on and critically examine their practices and beliefs in relation to this topic.